THE STRUCTURE OF THE LEGISLATIVE SENTENCE - Apresyan, Margaret (Foreign Languages for Special Purposes, 2024)
The present article highlights the main distinguishing features of a legislative text, mainly focusing on specific characteristics of the legislative sentence as the smallest unit of syntax in the legal discourse. The investigation of the legislative sentence underscores the specificity of syntactic structure of the Language for Law.
Keywords: legal documents; legislative sentence; legal discourse; Language for Law